What Are The Relative Merits of Interventions Used To Reduce the Occurrences of Repetitive Vocalisation in Persons with Dementia? – A Systematic Review - Randall, Edward William (2013)
Dementia has become a major health related issue and many people who have the progressive disease express behaviour that challenges. These behaviours such as repetitive vocalisation place large burdens on carers, family and on the individual themselves. Currently, there has been very little systematic evaluation of the evidence and so the aim of this review was to address the lack of research in this field. This systematic review explored the use of interventions that could be used within practice to reduce the occurrences of repetitive vocalisation in people with dementia. This included reviewing papers since 1997 that have initiated interventions through the use of three online databases. These were searched against two concept criteria of dementia and repetitive vocalisation. Data were accurately extracted using appropriate tools and processes to assess quality through a critical appraisal scoring mechanism. This systematic review identified eight relevant papers for inclusion and these assessed the implementation of eight separate interventions that could be used within practice. The best interventional approach was through the use of a staff training programme which was further broken-down into what the organisation could implement as well as individual responses either for the carer/staff or the person with dementia. The overall conclusions identified five recommendations that interventions should incorporate in order to have the best patient outcomes. These include making sure interventions are person-centred, individualised, adaptable, with the use of multiple approaches, carried out by staff trained in the identification of behaviours that challenge and ways to avoid triggering these behaviours. Study Aims and Objectives The aim of this systematic review is to explore the relative merits of nursing interventions currently being used reduce the occurrences of repetitive vocalisation expressed by people with dementia. The proposed question which titles this systematic review aims to achieve the following three objectives: